FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KECERDASAN EMOSIONAL ANAK TERHADAP PELAJARAN MATEMATIKA DENGAN MENGGUNAKAN ANALISIS FAKTOR - Elfrida Nasti; Taba Heri Setiawan; Hendro Warianto; Andi Andi; Gerry Gerry (LPPM Universitas Bina Bangsa, 2022)
The purpose of this study was to determine the factors that affect the level of emotional intelegence of children in mathematics at BIMBEL Rumpun Lestari trought a rduction process using the factor analysis method. Data colletion out by using a questionnaire method to 40 respondents. Based on the results of this factor analysis research, there are 2 factors that affect the level of emotional intelligence, namely factor 1 (F1) has a value of 0,630 (63,0%) and factor 2 (F2) has a value of 0,903 (90,3%). The correlation value of (F2) is greater than (F1), but the variance value of (F1) is greater than (F2), where the variand value (F1) =36,49% while (F2) =15,97%. So, the more dominant factor in influencing the level of emotional intelligence of children, namely (F1) with a variand value of 36,49% and is formed by internal and external facrors which greatly affect the level of emotional intelligence of children in mathematicts lessons at BIMBEL Rumpun Lestari